UJI BEBERAPA KONSENTRASI EKSTRAK TEPUNG DAUN SIRIH HUTAN (Piper aduncum L.) UNTUK MENGENDALIKAN PENYAKIT BUSUK BUAH KAKAO YANG DISEBABKAN OLEH Phytophthora palmivora Butl. - Wulandari, Ayu; Ali, Muhammad; Venita, Yunel (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The research aims to observe and to find the best concentration of wild betel leaf powder extract to control cocoa pod disease caused by Phytophthora palmivora Butl. The research had been conducted from October to December 2015 at the Laboratory of Plant Pathology, Faculty of Agriculture, University of Riau. The research was conducted experimentally using a completely randomized design consisting of 6 treatments and 4 replications. The treatments were: 0, 50, 100, 150, 200, and 250 g wild betel leaf powder/L water. The parameters observed were : colony diameter of P. palmivora, inhibition percentage on P. palmivora colony diameter, incubation period of the disease, intensity of the disease and effectiveness and ability level of powder extract of wild betel leaf on the disease as botanical fugicide. Data were analyzed statistically using by ANOVA, except for the parameters of effectiveness and ability level of fungicide was analyzed descriptively. To compare the mean of treatments with Duncan's New Multiple Range Test (DNMRT) at 5% level was used. The results showed that the concentrations of wild betel leaf powder extract could inhibit the growth ofP. palmivora and control cocoa fruit disease. Concentration of wild betel leaf powder at 200 and 250 g / L water gave a better ability to control P. palmivora andcocoa pod disease because they caused a smaller intensity of disease which were 45,71 % and 46.25%. Key words : Cocoa Fruit, P. palmivora , concentration of Piper aduncum L. leaf powder.